Kajian Pengembangan Database Sistem Informasi Jabatan Fungsional Badan Litbang Perhubungan - Hutapea, Sabungan Halomoan; Sinaga, Rosita (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2010)
777£ Infonnation and dntn center (Pusdntin) of TIU' Ministl J of Tmnsportntion /UIS developed personnelinformation st;stem to meet the needs of znfomwtion of Personnel Bureau of Ministn; of Transportation.711£ ccvailability of information prepared by Pusdatin, has not yet meets t/1.ese needs particularlyabout researcher's functional position.Tire process of achieving functional position follows tire applied rules and procedures, and involvesmany related agenci; which is timely consumed and diffirnlt to monitor manually. We s/wuldn't havefaced tlwse problems in this web based infomwtion teclznology em.777.e develapment of dntn base to support weh based infornwtion is e:cpected to prauide relillble, quickinfonnation, and also simplicihJ in nwnitonng the process.T71.ere are needed 14 prime files dan 24 support files to develop these database, which the codificationeach support files have been compiled to data element in order to the eficienhJ of storage, access time,and data process.Key words: Functional Position, Dntn Base